CLINICAL CHARACTERISTICS OF PATIENTS WITH AMYOTROPHIC LATERAL SCLEROSIS IN THE REPUBLIC OF SRPSKA - Lepir, Igor; Malešević, Milica; Dominović Kovačević, Aleksandra (Medicinski podmladak, 2019)
Introduction: Amyotrophic lateral sclerosis (ALS) is a rare, fatal and progressive neurodege- nerative disease which begins due to selective damage to motor neurons. The disease begins as spinal (spinal cervical, spinal lumbosacral and spinal thoracic form) and bulbar form. The diagnosis is set by using revised El Escorial criteria. Aim: Aims of the paper were determining demographic characteristics of ALS patients, ca- tegory of the disease and functional disability of patients using Revised Amyotrophic Lateral Sclerosis Functional Rating Scale (ALSFRS-R). Material and methods: In this cross-sectional study, medical histories of ALS patients, which were diagnosed at the Clinic of Neurology of the University Clinical Center of the Republic of Srpska, were examined. Demographic characteristics, initial form of the disease, category of disease (using revised El Escorial criteria), functional disability (using ALSFRS-R) and dia-gnostic delay were analyzed. Results: This study included 30 patients, 20 (67%) were male, 10 (33%) were female. The ALS began at 57 ± 12 years, and average diagnostic delay was 10 months. The disease started as a spinal form in 26 (87%) patients, out of which 13 (43%) had spinal cervical, 12 (40%) spinal lumbosacral and 1 (3%) spinal thoracic form of disease. The initial bulbar form was reported in 4 (13%) patients. The average ALSFRS-R score was 33,5. Patients with a spinal lumbosacral form of the disease had statistically significant lower score of ALSFRS-R (p = 0.048) which indicates bigger functional motoric disablement, compared to other forms of disease. Low values of ALSFRS-R are correlated with more accurate diagnosis, according to the revised El Escorial criteria. Conclusion: Results of this study showed that ALS is more frequent and occurs earlier in men. The disease most commonly started as spinal cervical form. Patients with spinal lumbo-sacral form of the disease had significantly lower values of ALSFRS-R which indicates a faster progression of the disease. As patients acquire lower ALSFRS-R scores and greater disability, they progress to the definite ALS category.